KNOWLEDGE COMPETENCY ANALYSIS OF HEALTH WORKERS AT SURABAYA COASTAL AREA PRIMARY HEALTH CENTER - Wildan Taufik Raharja; Lunariana Lubis; Agus Wahyudi (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
The quality of services at the Primary Health Center (Puskesmas) and the level of utilization of Puskesmas services are closely related to the competency of human resources providing services to the community. Quality health services can provide satisfaction to patients in accordance with the average level of satisfaction of the population as well as procedures for conducting them according to established professional and ethical standards.The purpose of this study to map the competency of knowledge of health workers at Surabaya Coastal Area Primary Health Center. The location of this research is at Puskesmas located in the North Coast of Surabaya, namely Sidotopo Primary Health Center and Sawah Pulo Primary Health Center. This research uses a qualitative approach with a case study research strategy. Then the technique for determining the informant was done using purposive sampling and snowball sampling. This study analyzed the competency of health workers' knowledge with 3 indicators, namely general knowledge, special knowledge and typical knowledge.The results in this study are knowledge competency of health workers at Surabaya coastal area health center is still not good. The majority of health workers do not have special knowledge or specialization. Human resource development is needed by the relevant agencies.Keywords: Competence, Community Satisfaction